BIMBINGAN PRIBADI SOSIAL UNTUK MENGIMPLEMENTASIKAN PENDIDIKAN KARAKTER TERHADAP SISWA SEKOLAH DASAR DENGAN TEKNIK TOKEN ECONOMY: PERSONAL SOCIAL GUIDANCE TO IMPLEMENT CHARACTER EDUCATION IN ELEMENTARY SCHOOL STUDENTS WITH TOKEN ECONOMY TECHNIQUES - Rini Susanti; Sovi Navisah (Universitas Singaperbangsa Karawang, 2021)
The purpose of this study was to determine personal effectiveness in implementing character education for elementary school students using token economy techniques. This study used a quantitative approach with a quasi-experimental method and a nonequivalent design. The population in this study were 226 students of SD Negeri 1 Jatianom for the 2019/2020 academic year, and using clustering sampling. Data collection using character education instruments. The results of the posttest scores in the experimental group using paired t test with a significance value of .000. The significance value .000 is <0.05, so there is a significant difference between before receiving treatment and after receiving treatment. Can provide personal social guidance with token economy techniques that effectively implement character education.